FROM OUTSOURCING TO SMARTSOURCING DRIVING INNOVATION AND GROWTH THROUGH OUTSOURCING FOR SMES - Munawaroh Munawaroh; Syamsul Hadi Senen; Rofi Rofaida (Nindikayla Institute, 2023)
There is some evidence in this article regarding the role of outsourcing for SMEs and the change in outsourcing to smartsourcing, seen in conventional outsourcing that has now shifted to advances in IT technology through big data and other applications. The review of this article is obtained from 35 scientific articles published by the author, where the majority of articles are research methods with case studies. The results of qualitative thematic descriptive analysis from Outsourcing to Smartsourcing Encouraging Innovation and Growth through Outsourcing For SMEs can be seen from SMEs that have expanded outsourcing in almost every area of ​​operation, such as human resource management (HRM), IT, peripheral tasks, transaction levels, professions. and strategies, enhancing core competencies, and so on. The outsourcing of technology makes outsourcing into smartsourcing which is considered more effective, efficient and developing globally